OPTIMASI FERMENTASI PADA PEMBUATAN EKSTRAK TEMULAWAK SEBAGAI BAHAN BAKU ES KRIM (OPTIMATION OF FERMENTATION ON PRODUCING TEMULAWAKS EXTRACT AS RAW MATERIAL OF ICE CREAM) - Puspitojati, Endah; Santoso, Hadi (Jurnal Ilmu-Ilmu Pertanian, 2012)
Temulawak has a distinctive image of a bitter taste that causes some people are not willing to consume it. Though it contains an active compound such as curcumi-noids which has many health benefits for our bodies. This study aimed to minimize the bitter taste of temulawak through optimization of fermentation using yeast and to utilize the optimum one as raw material for temulawaks ice cream. The methods used in this study is the Response Surface Methods using Design Expert Version 8.0 program that generated into 13 running formula. From the total formula obtained optimum fermen-tation of temulawaks extracts which required yeast as much as 15 grams and 24 hours of fermentation time with curcuminoids content of 1.979%, 2.54 score of taste, 3.35 score of color, 2.78 score of flavor. Desirability of the product value reached 68.0%. Formula elected to use as raw material for producing ice cream. The result of ice cream showed that it had better quality of ice cream than used extracts without fermen-tation with an average hedonic score (a level of preference) at 3.98 and content of curcuminoids reached to 0.221%.